Celiac disease-related hepatic injury: Insights into associated conditions and underlying pathomechanisms. Issue 2 (February 2016) - Marciano, Francesca; Savoia, Marcella; Vajro, Pietro
Abstract: Background: Celiac disease (CD) is the most common autoimmune enteropathy. Clinical manifestations may range from a typical malabsorption syndrome to several apparently unrelated extra-intestinal symptoms. Aim: Here we specifically focus on the spectrum of CD-related liver disorders and the underlying pathomechanisms. Methods: A computer-based search up to August 2015 was completed using appropriate keywords. References from selected papers were also reviewed and used if relevant. Results: An unexplained hypertransaminasemia with nonspecific histologic hepatic changes is the most common hepatic presentation. CD however can coexist with a number of liver disorders such as Autoimmune Hepatitis, Autoimmune Cholangitis, Primary Biliary Cirrhosis and Primary Sclerosing Cholangitis requiring a specific treatment in addition to gluten-free diet. CD has also been associated with Viral Hepatitis, Fatty Liver, Non-Alcoholic Steatohepatitis and some severe cryptogenic hepatopaties in the liver transplantation list. Pathomechanisms underlying hepatic injury in CD are multiple, appear still not completely defined and may probably co-occur. Conclusions: An ever-increasing number of CD-related liver injuries exist, probably representing a continuum of a same disorder where genetic predisposition, timing, and duration of previous gluten exposure might influence the reversibility of liver damage. Evidences, although not conclusive, support therefore testing for CD also in cryptogenic hepatobiliary conditions where the relationship with CD has not yet been fully investigated.